Referral for lung transplantation: experience of a Birmingham Adult Cystic Fibrosis Centre between 1987 and 1994. Issue 3 (March 1996) - Ryan, P J; Stableforth, D E
Abstract : BACKGROUND: Whilst much is known of the outcome of lung transplantation for patients with cystic fibrosis, less is known about those patients who are either not referred for transplantation or who die before a donor is available. The referral practice and outcome of all the cystic fibrosis patients in one clinic was documented, whether or not they were assessed for lung transplantation. The results give a perspective on the impact of the current transplantation programmes on the adult cystic fibrosis population as a whole. METHODS: A retrospective study was made of patient deaths and referrals for lung transplantation between 1987 and 1994 from the Adult Cystic Fibrosis Clinic at Birmingham Heartlands Hospital. RESULTS: The Birmingham Heartlands Adult Cystic Fibrosis Clinic has managed 192 patients since its beginning and currently cares for 141 patients. Since 1987 there have been 16 deaths in patients with cystic fibrosis who were considered unsuitable for lung transplantation. Of 49 patients referred for lung transplantation, 47 were accepted on to a provisional or active waiting list. The mean (SE) age at referral was 23.9 (0.7) years and mean (SE) forced expiratory volume in one second (FEV1) was 0.87 (0.04) 1. Fourteen patients died whilst awaiting transplantation and 19 received donor lungs. There have been 10 deaths in the transplanted group. Survival following transplantation was 58% at one year and 52% at two years. CONCLUSION: Most of the deaths that occurred in the Cystic Fibrosis Clinic were in patients who either were not considered suitable for transplantation or were still awaiting transplantation. Whilst lung transplantation is the focus for many adults with cystic fibrosis, lack of donor organs has limited the impact of transplant programmes on the clinic.